2018
DOI: 10.1038/s41419-017-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

MCL-1 is a prognostic indicator and drug target in breast cancer

Abstract: Analysis of publicly available genomic and gene expression data demonstrates that MCL1 expression is frequently elevated in breast cancer. Distinct from other pro-survival Bcl-2 family members, the short half-life of MCL-1 protein led us to investigate MCL-1 protein expression in a breast cancer tissue microarray and correlate this with clinical data. Here, we report associations between high MCL-1 and poor prognosis in specific subtypes of breast cancer including triple-negative breast cancer, an aggressive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(166 citation statements)
references
References 56 publications
7
157
0
2
Order By: Relevance
“…Experimental validation in a panel of breast cancer cell lines coupled with genomic analyses in large patient cohorts identified the MCL1 level as a predictor for response to combined inhibition of MCL1 and BETis. MCL1 amplification is a well-characterized prognostic factor in breast cancer (12,33). Here we showed that MCL1i were effective in cells with MCL1 gain or amplification and that breast cancer cells are further sensitized to MCL1 inhibition when combined with BETis.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Experimental validation in a panel of breast cancer cell lines coupled with genomic analyses in large patient cohorts identified the MCL1 level as a predictor for response to combined inhibition of MCL1 and BETis. MCL1 amplification is a well-characterized prognostic factor in breast cancer (12,33). Here we showed that MCL1i were effective in cells with MCL1 gain or amplification and that breast cancer cells are further sensitized to MCL1 inhibition when combined with BETis.…”
Section: Discussionmentioning
confidence: 73%
“…With the introduction of specific inhibitors, MCL1 has become an actionable therapeutic target. Broader impact of MCL1 inhibitors could be achieved by selectively inducing survival dependencies that make use of higher levels of MCL1 (11)(12). For example, targeted agents that can generate therapeutic stress and MCL1-driven anti-apoptotic dependence may induce a clinically relevant vulnerability even in cases that carry low-level MCL1 gains.…”
Section: Introductionmentioning
confidence: 99%
“…MCL1 gene is one of the B‐cell lymphoma 2 (BCL‐2) family, which monitors and regulates cell apoptosis. Failure to initiate apoptosis promotes the development of tumors and prevents cancer therapy‐induced cell death . BCL‐2 family comprises antiapoptotic and protoapoptotic members.…”
Section: Introductionmentioning
confidence: 91%
“…Failure to initiate apoptosis promotes the development of tumors and prevents cancer therapy-induced cell death. 11 BCL-2 family comprises antiapoptotic and protoapoptotic members. The overexpression of the antiapoptotic members of the BCL-2 family is a major proliferative factor of OVC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mcl-1 is an anti-apoptotic member of the Bcl-2 family proteins which is frequently upregulated in cancers to promote cell survival [96–99]. Under normal conditions, Mcl-1 associates with the proapoptotic BAK protein to maintain BAK in an inactive state whereas downregulation of Mcl-1 proteins is triggered by DNA damage, such as infection by viruses [100].…”
Section: Substrates Of Huwe1mentioning
confidence: 99%